IMPLIKATUR DALAM TALK SHOW RUMPI NO SECRET DI STASIUN TELEVISI TRANS TV - Annisa Asmar Cholby; Mangatur Sinaga; Charlina Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is about Implicature in the Rumpi No Secret Talk Show on the Trans TV Television Station. This study aims to describe what forms of implicature and implicature markers in the Rumpi No Secret Talk Show on the Trans TV Television Station. The type of research is qualitative research. The source of data in this research is the dialogue between the presenter and the speaker or the audiance on the Rumpi No Secret Talk Show on the Trans TV Television Station that is aired again on youtube. Data collection techniques of this research are SBLC technique and documentation technique. The data analysis technique used in this study is the determining element sorting technique. The results of this study are as follows. First, the forms of implicature in the Rumpi No Secret Talk Show on the Trans TV Television Station, namely 1) conventional implicature and 2) conversation implicature. Second, implicature markers in the Rumpi No Secret Talk Show on the Trans TV Television Station, namely 1) implicature marker of quality maxim deviation, 2) implicature marker of quantity maxim deviation, 3) implicature marker of relevance maxim deviation, 4) implicature marker of implementation maxim deviation, 5) implicature marker of quantity maxim and implementation maxim deviation, 6) implicature marker of quantity maxim and quality maxim deviation, and 7) implicature marker of quantity maxim and relevance maxim deviation.Key Words: Implicature, Talk Show, Maxim Deviation